(3GdCReI GdEbJUGOjI GdeUQjI YbH KhQI (B25 (3jfGjQ h BKGQgG Ydi Shb GdChQGb GdeGdjI(B/ s - (3CSeGA SjO aGQhb MSf s; (3SjO Wg HOhjs; (3LGeYI GdbGgQIs (3cdjI GdMbhbs ((3GdbGgQI (B: s (3cdjI GdMbhb(B-(3LGeYI GdbGgQI,s, 2017)
(3gOaJ GdOQGSI GdMGdjg Edi HMK eOi JCKjQ GdCReI GdEbJUGOjI GdeUQjI YbH KhQI (B25 (3jfGjQ Ydi COGA Shb GdChQGb GdeGdjI GdeUQi(B: (3hPdc Yf WQjb JMdjd YOO ef GdeDTQGJ GdEbJUGOjI MJi fSJWjY JMOjO hVY GdEbJUGO GdeUQj(B: (3Ke HjGf eOi JCKjQgG Ydi COGA Shb GdChQGb GdeGdjI GdeUQi eeKdkG aj COGA eDTQ (BEGX30 (3hPdc aj GdaJQI ef (B2007-2014 , (3hbO bGeJ GdOQGSI Ydi aQV Cf GdCReI GdEbJUGOjI GdeUQjI HYO KhQI (B25 (3jfGjQ CKQJ Ydi COGA Shb GdChQGb GdeGdjI GdeUQj(B: (3MjK Cf GdCReI eG gj EdG fJGL deTGcd eJfhYI ShGA SjGSjI Ch GbJUGOjI(B: (3hdgG CfhGY hCHYGO CgegG GdEbJUGOjI hGdELJeGYjI hGdSjGSjI(B: (3hbO EYJeOJ GdHGMKI GdefgL GdhUai GdJMdjdi ef NdGd GdJYHjQ Yf GdhGbY GdEbJUGOi HTcd cjai HgOa JTNjUI hJMOjO NUGFUI hGdJYQa Ydi fbGW GdbhI hGdVYa aj VhA GdXQha GdbGFeI dJMOjO MLe GdCReI , hMjK Cfg HEYJHGQ Shb GdChQGb GdeGdjI GdeQBg GdJj JYcS GdhVY GdEbJUGOi hGdSjGSi GdYGe , abO JCKQ HcGaI GdCMOGK GdSjGSjI hGdJOGYjGJ GdEbJUGOjI GdJj YGfJ efgG eUQ YbH KhQI (B25 (3jfGjQs
(3GWQhMI (B((3OcJhQGg(B) - (3LGeYI GdbGgQI (B- (3cdjI GdMbhb (B- (3bSe GdeGdjI GdYGeI hGdJTQjY GdVQjHj, (B2017 s
(3HHdjhLQGajG(B: (3UaMGJ (B508-530s
(3GdedNU HGddZI GdYQHjIs
Keywords: (3GdChQGb GdeGdjIs; (3GdTQcGJ GdebjOI aj GdHhQUg GdeUQjg s; (3GdTQcGJ GdeUOQI s; (3GdSfOGJ s; (3Shb GdChQGb GdeGdjI s; (3GdeMaXI GdeGdjI s; (3GdYGFOs; (3GdfXGe GdQGSeGdj s; (3bGfhf VeGfGJ h MhGaQ GdGSJKeGQ Qbe (B8 (3dSfg (B1998s; (3GdGjOGY h GdbjO GdeQcRj ddGhQGb GdeGdjI s; (3SYQ UQa GdLfjI GdeUQjs; EGX100; EGX 30; (3GdGMJjGWj GdOhdjs; (3MLe GdOjf s; (3GdgjFI GdYGeI ddQbGHg GdeGdjg s; (3GdHhQUg GdeUQjI s; (3GdMhceI GdeUQjI s; (3GdJVNe aj GdShb GdeUQjs; (3QSGFd LGeYjIs -- (3LGeYI GdbGgQIs -- (3GdeGdjI GdYGeI hGdJTQjY GdVQjHjs